Analisis Perkembangan Pemanfaatan Energi Listrik Tenaga Bayu Sebagai Energi Alternatif - Febby Putri Wulandari; Yushardi; Sudarti (CV. ITTC INDONESIA, 2023)
Some renewable alternative energy sources are air, wind, sun and biomass. This alternative energy source is part of renewable energy. An energy sourced from unlimited amounts of natural resources is called renewable energy. Wind energy is a renewable alternative energy source that does not cause pollution or air pollution. Uneven heating of the surface by the sun can form wind. So cold air will fall and hot air will rise, this air exchange causes wind. In simple terms, if the sun continues to shine on the earth, wind will continue to form. Wind Power Plant or PLTB is a structure or facility that uses wind turbines installed on top of tall towers which are driven by wind energy to produce electricity. The wind blowing through the turbine turns the turbine wheel or rotor. This rotation is then converted into kinetic energy which can be used to produce electricity using a generator. Wind turbines that utilize wind energy do not produce dangerous chemical compounds, greenhouse gases and carbon dioxide emissions. This means that the use of wind energy does not cause pollution, whether land, water or air pollution.